2007
DOI: 10.4028/www.scientific.net/kem.361-363.47
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Characterization of Mg-Containing Nano-Apatite

Abstract: Nano-crystalline Mg-containing hydroxyapatite (Mg·HAp) were prepared by a wet chemical method, for which selective adsorption of proteins was examined, taking bovine serum albumin (BSA) and a pathogenic protein β2-microglobulin (β2-MG) as the model proteins. Increase in the Mg content led to smaller crystallites and larger specific surface area (SA) of Mg·HAps as well as zeta potential, while the amount both of BSA and β2-MG adsorption on Mg·HAp particles. It is thus concluded that the adsorption of BSA and β2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…Mg•HAp particles were synthesized by a precipitation processing method, where the molar ratio Mg/(Mg+Ca) was varied in the range from 0 to 0.3 for the target composition (Ca+Mg) 5 (PO 4 ) 3 OH. The preparation procedure was described elsewhere [1]. The crystalline phases were identified by using XRD technique.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Mg•HAp particles were synthesized by a precipitation processing method, where the molar ratio Mg/(Mg+Ca) was varied in the range from 0 to 0.3 for the target composition (Ca+Mg) 5 (PO 4 ) 3 OH. The preparation procedure was described elsewhere [1]. The crystalline phases were identified by using XRD technique.…”
Section: Methodsmentioning
confidence: 99%
“…We have previously reported that Mg-containing hydroxyapatite (Mg•HAp) exhibited relatively low protein adsorption properties for bovine serum albumin (BSA) and β 2 -microglobulin (β 2 MG) [1]. This result was explained by considering the small crystallite size accompanied by the inter-particle spaces with appropriate size, which can trap these proteins.…”
Section: Introductionmentioning
confidence: 99%